2010
DOI: 10.1073/pnas.0914100107
|View full text |Cite
|
Sign up to set email alerts
|

The structure of ribosome-lankacidin complex reveals ribosomal sites for synergistic antibiotics

Abstract: Crystallographic analysis revealed that the 17-member polyketide antibiotic lankacidin produced by Streptomyces rochei binds at the peptidyl transferase center of the eubacterial large ribosomal subunit. Biochemical and functional studies verified this finding and showed interference with peptide bond formation. Chemical probing indicated that the macrolide lankamycin, a second antibiotic produced by the same species, binds at a neighboring site, at the ribosome exit tunnel. These two antibiotics can bind to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 63 publications
2
40
0
Order By: Relevance
“…The [IC 50 ] of LM (Table 1) shows that compared to Ery it exerts a weaker inhibition of ribosomes by a few orders of magnitude (11). A comparison of the structures of LM-D50S complex with the Ery-50S complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The [IC 50 ] of LM (Table 1) shows that compared to Ery it exerts a weaker inhibition of ribosomes by a few orders of magnitude (11). A comparison of the structures of LM-D50S complex with the Ery-50S complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, as these differences are rather modest, it was assumed that LM should bind to the ribosome at the nascent protein exit tunnel in similar position and mode as erythromycin. Interestingly, although LM and LC are able to bind simultaneously, erythromycin disrupts the binding of LC (11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2 This idea proved to be true by a collaborative work with Drs Yonath and Mankin. 54 Furthermore, crystallographic analysis and chemical probing showed that two antibiotics were bound to a different ribosome site, lankacidin to the peptidyl transferase center and lankamycin to the nascent peptide exit tunnel, leading to a synergistic inhibition of peptide formation. A similar super-cluster for cephamycin and clavulanic acid was found in S. clavuligerus, 55 where the two metabolites function synergistically as an antibiotic and a b-lactamase inhibitor, respectively, and their biosynthesis is regulated by the SARP gene ccaR.…”
Section: Biosynthesis Of Lankacidin and Lankamycinmentioning
confidence: 99%